PELATIHAN TATA CARA BERSUCI KEPADA ANAK-ANAK DAN REMAJA DI DESA PANTAI HARAPAN JAYA - Ubaidillah Ubaidillah; Abdul Ghofur; Irham Irham (An-Nizam, 2023)
Worship is the main task that Allah SWT has entrusted to humans while standing on earth. There are many ways of worship, which if summarized into two types, namely mahdhah worship (pure / without intermediaries) and ghairu mahdhah worship (impure / through intermediaries) where worship performed by Muslims has several conditions so that their worship is accepted, one of which is purification. Based on the analysis of the problems received by the author from the community in Pantai Harapanjaya Village, there are still many children and adolescents who do not fully understand and practice the correct procedures for purification according to the guidance of Islamic law. Because of the problems that exist, the author uses the lecture and demonstration method on the material for correct purification training procedures according to the guidance of Islamic law which are held in two meetings, where the first meeting uses the lecture method which is held at the Al-Husna Mosque in Bulak Hamlet and the second meeting uses the lecture method. demonstration method carried out in the Saung Ilmu Bulak Hamlet. The results of the conclusions from these two activities include, firstly increasing understanding and increasing children and youth in carrying out the practice of purification properly according to Islamic sharia guidelines and secondly increasing trust in the community and parents towards children and adolescents that they have been able to become the golden generation to continue the struggle for progress in Harapanjaya Beach Village with the initial capital of having a pure soul from an early age.